Cathodoluminescence of self-organized heterogeneous phases in multidimensional perovskite thin films - Cortecchia, Daniele (2020)
Multidimensional hybrid perovskites are becoming increasingly important for photovoltaic and light-emitting applications because of their improved moisture stability, unique luminescence, and transport properties. Little is known, however, about the phase distribution and self-organization properties of multidimensional perovskite thin films. In this work, we combine steady-state and time-resolved cathodoluminescence microscopy with photoluminescence techniques and reveal with unprecedented resolution the characteristic self-assembly of heterogeneous phases of perovskites with different dimensionality, driven by uneven redistribution of methylammonium cations during film formation. Our findings provide fundamental insights for the rational design of complex multidimensional perovskite systems with improved stability and emissive properties.